Kontribusi Daya Ledak Otot Tungkai dan Panjang Tungkai Terhadap Hasil Lari 50 Meter pada Siswa Kelas X SMAN 2 Rambah Kabupaten Rokan Hulu - Mahesa, Diefki; Rezki, Rezki (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to determine the contribution of leg muscle explosive power and leg length to the 50-meter run in class X SMAN 2 Rambah, Rokan Hulu Regency. The type of this research is multiple correlations. The population and sample in this study were 30 class X students of SMAN 2 Rambah, Rokan Hulu Regency. The research instruments used were the leg muscle explosive power test, the leg length test, and the 50-meter running test. The data analysis technique used is to test your correlation value. Based on the results of the research that has been done, it can be concluded that 1) there is a contribution of leg muscle explosive power to the 50 meter run in class X students of SMAN 2Rambah Rokan Hulu Regency by 19.27% with a value of rcount = 0.439 > rtable = 0.361, 2) there is acontribution leg length to the results of running 50 meters in class X SMAN 2 Rambah Rokan HuluRegency by 14.90% with rcount = 0.386 > rtable = 0.361, 3) there is a contribution of leg muscleexplosive power and leg length to running 50 meters in class X SMAN students 2 Rambah Rokan Hulu Regency by 23.81% with rcount = 0.488 > rtable = 0.361.